Automatic digital audiometer for mass hearing examinations - LIPOWCZAN, Adam; RABSZTYN, Tadeusz (Archives of Acoustics, 1979)
This paper presents the lay-out and design of an automatic digital audio-meter. All audiometernctions are programmable thus eliminating the operator errors associated with conventional designs. The design is based on a modular concept resulting in simplification in servicing and the interchangeability of modules between various types of audiometers based on the above concept. The audiometer has been tested and is presently at the stage of serial production.